Branding “Tara La No Ate” pada Indonesia Creative Cities Festival (ICCF) - Lisda Ariani Simabur (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The first aspect of the promotion of communication strategies can be concluded as